2022
DOI: 10.3390/medicina58081066
|View full text |Cite
|
Sign up to set email alerts
|

Infections in Burn Patients: A Retrospective View over Seven Years

Abstract: Backgroundand objectives: Burn patients represent a challenging cohort because the injuries entail a vulnerability to colonisation by microorganisms. The ensuing infections can lead to serious complications and, in many cases, to the death of the burn patient. Surgical intervention and wound dressings, as well as antibiotic treatment, are crucial for optimising the treatment of the patient. Materialand Methods: In this retrospective analysis, we analysed the treatment course, antibiotic therapy, and general co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 21 publications
0
5
0
2
Order By: Relevance
“…However, within a few days, Gram-positive strains, such as Staphylococcus aureus, coagulase-negative Staphylococcus, and Streptococcus spp., start to colonize the wounds from deeper structures (hair follicles and glands). In the second phase, a Gram-negative shift takes place, where P. aeruginosa, E. coli, and Proteus are the predominant isolates [18,19,20]. If left untreated, this colonization can lead to infection [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…However, within a few days, Gram-positive strains, such as Staphylococcus aureus, coagulase-negative Staphylococcus, and Streptococcus spp., start to colonize the wounds from deeper structures (hair follicles and glands). In the second phase, a Gram-negative shift takes place, where P. aeruginosa, E. coli, and Proteus are the predominant isolates [18,19,20]. If left untreated, this colonization can lead to infection [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Представленный в нашем исследовании микробный спектр ожоговых ран свидетельствует об инфицировании представителями внутрибольничной микробиоты стафилококками, неферментирующими грамотрицательными бактериями и энтеробактериями. Указанные микроорганизмы характерны для многих ожоговых центров, и полученные результаты не противоречат данным других исследований [4,[6][7][8][9].…”
Section: обсуждение полученных данныхunclassified
“…В этот период важным компонентом лечения становится антибактериальная терапия. При этом неправильное назначение антибиотиков может способствовать развитию резистентности к антибиотикам, ускорять развитие мультирезистент ных микробов, а также негативно влиять на экосистему отделения интенсивной терапии [7]. Поэтому решающее значение в выборе противомикробного препарата имеют результаты микробиологического исследования и данные локальной антибиотикорезистентности [8,9,10].…”
unclassified
“…It has been reported that long-standing burn patients often had fatal outcomes, including death (42-65%) because of infection [97][98][99][100][101]. Ag-SD is a pharmaceutical product often prescribed to stave off, control, and treat infectious disorders in burn lesions.…”
Section: Silver Sulfadiazine (Ag-sd) In Burn Infection Controlmentioning
confidence: 99%